Table 1_From wisdom to efficacy: the mediating role of positivity ratio in the relationship between university students’ knowledge strengths and academic self-efficacy.docx - Sitong Li (12974639) (2025)
Background Grounded in positive psychology and the broaden-and-build theory, this study examined how VIA-IS Wisdom and Knowledge predicts academic self-efficacy via the positivity ratio, distinguishing Learning Ability Efficacy and Learning Behavior Efficacy. Drawing on positive psychology and the broaden-and-build theory, this study tested a mechanism model linking wisdom and knowledge strengths → positivity ratio → academic self-efficacy. Two facets of academic self-efficacy were distinguished—learning ability efficacy and learning behavior efficacy—to clarify whether emotions contribute differently to confidence in understanding versus managing learning tasks. Methods A cross-sectional online survey was conducted with 531 Chinese university students (73% female, 27% male; 34% urban Hukou, 66% rural; recruited from five comprehensive/normal universities in southwestern China across education, psychology, management, and engineering majors). Measures included the wisdom and knowledge dimension of the VIA-IS, the revised Chinese Positive and Negative Affect Schedule for computing positivity ratio, and the Academic Self-Efficacy Scale. Data were analyzed by SPSS 27.0 using correlation, mediation and multivariate GLM analyses to test the hypothesized strengths → emotions → efficacy pathway. Results Students with higher wisdom and knowledge strengths and higher positivity ratios reported stronger academic self-efficacy (r = 0.42–0.47, p < 0.01). Emotional balance partially mediated this link [indirect effect = −0.06, 95% CI (−0.11, −0.03)], suggesting that positive affect serves as a bridge between cognitive strengths and confidence in learning. This emotional pathway was significantly stronger for ability-related efficacy than for behavior-related efficacy (Δ = 0.10, p < 0 0.001), indicating that feeling positive is especially crucial for beliefs about learning competence. Conclusion The correlation between wisdom and knowledge strengths and academic self-efficacy is twofold: direct and indirect. The direct correlation is evident through positive emotions, while the indirect correlation manifests through the enhancement of academic self-efficacy. The findings emphasize that cognitive strengths and emotional balance collectively foster students’ motivation and learning confidence. Interventions that integrate strength development, emotional regulation, and self-efficacy building may therefore be particularly effective in higher education settings.